2009
DOI: 10.1002/asi.21202
|View full text |Cite
|
Sign up to set email alerts
|

Image use within the work task model: Images as information and illustration

Abstract: With increasing sophistication in technology has emerged a growing interest in accessing images for personal and work purposes. In this research we investigated the use of images as data-for the information contained within the image, and as an object to illustrate. Thirty journalists and historians from academic and professional work settings were interviewed using a series of semistructured questions regarding how they use images (for information or for illustration) and the types of image attributes used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 46 publications
2
40
0
1
Order By: Relevance
“…Applying these categories to Fidel's (1997) data-object image continuum, they report that 53.6 percent of image use in their study was object (illustration) oriented, 24 percent was data (information) related, and 21.4 percent was both. These figures, reflecting Fidel's image use continuum, support the findings of the study by McCay-Peet and Toms (2009).…”
Section: Related Studiessupporting
confidence: 88%
“…Applying these categories to Fidel's (1997) data-object image continuum, they report that 53.6 percent of image use in their study was object (illustration) oriented, 24 percent was data (information) related, and 21.4 percent was both. These figures, reflecting Fidel's image use continuum, support the findings of the study by McCay-Peet and Toms (2009).…”
Section: Related Studiessupporting
confidence: 88%
“…More recently, as an important way of investigating users' image information needs, contextual factors affecting image needs and search behaviours, such as image use, are now being examined [1,[3][4][5]. In this sense, this study aims to examine the general users' needs for images in context of image uses for non-domain-specific collections.…”
Section: Image Needs In Context Of Usesmentioning
confidence: 99%
“…Although there have not been any clear definitions and constituent elements regarding the context of the images [3][4][5], the context of the users and their information needs is a significant factor. In particular, in various contexts, image use has been recognized as one of the crucial elements in realizing the image needs of users [1]. As Fidel [6] pointed out, unlike textual documents, images can be used in diverse ways (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that images may have several types of functions in different contexts, such as illustrative, informative, persuasive, attention-related (e.g., attracting and holding attention), aesthetic (e.g., adorning something), and affective functions (e.g., establishing a mood). Further work has been conducted for example on the effects of work task on the use of images as illustration or information (McCay-Peet & Toms, 2009). In categorization, each image is assigned to a group of images, creating a link between these images.…”
Section: Attributes Beyond Contentmentioning
confidence: 99%